PERCEPTIONS OF LECTURERS AND STUDENTS OF THE JAPANESE LANGUAGE EDUCATION PROGRAM AT UNJ TOWARDS THE YOMUJP WEBSITE IN ENCHANCING JAPANESE READING SKILSS AT N4 LEVEL - Hamdi, Muhammad Ali; Syam, Muhammad Ali Sulaiman; Humaira, Nadhira Shafa (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2024)
This study aims to analyze the perceptions of lecturers and students of Japanese Education Program of Jakarta State University towards the website yomujp.com/n4 in improving Japanese reading skills at the N4 level. The research method used was qualitative with a Likert scale to measure respondents' responses. The respondents for this research were 43 respondents consisting of lecturers and students of the Japanese Language Education Study Program, Jakarta State University. Data were collected through in-depth interviews and questionnaires distributed to lecturers and students who have used the website. The results showed that the majority of lecturers and students gave positive responses to yomujp.com/n4. They consider this website to be very helpful in providing readings that match the difficulty level of JLPT N4. The material presented on this website is considered very useful because it is structured and complete, covering various JLPT levels from N5 to N1. In addition, the additional N6 level is very helpful for beginners who have not been able to read Hiragana and Katakana. The advantages of the yomujp.com/n4 media site are the varied and structured learning materials, namely these teaching materials are equipped with furigana, pictures and audio recordings, which contribute to improving understanding, pronunciation and interest in learning Japanese, user-friendly site design, Practical learning features. Disadvantages of the yomujp.com/n4 site are the variation of the material and limited interactivity and exercises.